Epidemiologic and Clinicopathological Characterization of Feline Mammary Lesions - Fernanda R. Souza; Isabella S. Moreira; Artur A. Dariva; Karen Y. R. Nakagaki; Camila C. Abreu; Débora Balabram; Geovanni D. Cassali (Veterinary Sciences, 2024)
Most lesions found in the mammary glands of cats are malignant, with aggressive behavior and unfavorable prognosis. Studies on the epidemiologic and clinicopathological characteristics of mammary lesions in cats are scarce. The present study aimed to evaluate those characteristics and to correlate them with survival in cats. Mammary specimens were selected from 418 domestic cats that underwent surgical removal with or without lymphadenectomy. The cats and mammary lesions were evaluated for epidemiologic, clinical, and pathologic characteristics. Cats with malignant neoplasms were older than cats with benign neoplasms and non-neoplastic lesions; 858 lesions were identified, including sporotrichosis, basaloid carcinoma, and benign phyllodes, described for the first time in cats. Tubulopapillary and cribriform carcinomas were the most common malignant tumors found and were very similar in characteristics such as marked anisocytosis/anisokaryosis, high mitotic count (score 3) (p < 0.001), and presence of necrosis (p = 0.005). The association between advanced age and malignancy, as well as the description of new lesions, emphasizes the importance of population studies in cats to understand the behavior of the disease and to draw attention to diagnoses that should be considered in routine care.